2020
DOI: 10.3390/cancers12071789
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Vincristine Related to Infusion Duration and Peripheral Neuropathy in Pediatric Oncology Patients

Abstract: Vincristine (VCR) is frequently used in pediatric oncology and can be administered intravenously through push injections or 1 h infusions. The effects of administration duration on population pharmacokinetics (PK) are unknown. We described PK differences related to administration duration and the relation between PK and VCR-induced peripheral neuropathy (VIPN). PK was assessed in 1–5 occasions (1–8 samples in 24 h per occasion). Samples were analyzed using high-performance liquid chromatography/tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Data on VCR PK and SNP’s were also collected as part of this trial, but analyses of these data was beyond the scope of this paper. Data of this trial regarding administration duration related to PK were published separately [ 42 ]. Potentially, infusion of VCR in one-hour could lead to an increased risk of extravasation, which is dangerous in VCR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data on VCR PK and SNP’s were also collected as part of this trial, but analyses of these data was beyond the scope of this paper. Data of this trial regarding administration duration related to PK were published separately [ 42 ]. Potentially, infusion of VCR in one-hour could lead to an increased risk of extravasation, which is dangerous in VCR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was demonstrated that certain genetic aberrations, like a single nucleotide polymorphism in centrosomal protein 72 (CEP72) influence the development of VIPN in children. 39 Following this, studies could be undertaken that use these genetic aberrations to dose modify VCR in certain populations requiring more or less. Another approach would be to study pharmacokinetics of VCR.…”
Section: Discussionmentioning
confidence: 99%
“…There is no established target VCR exposure yet, but reliable VCR PK data have been collected that could contribute to this. 13 , 40 When the target VCR exposure is known, VCR doses could be adapted accordingly. Finally, improving administration duration of VCR can optimize VCR treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study assessing pharmacokinetics of vincristine in 74 pediatric patients, lower vincristine metabolite concentrations were associated with increased CIPN severity ( 45 ). Another study assessed vincristine pharmacokinetics in 35 patients receiving vincristine via push or 1 h infusions and found intercompartment clearance of vincristine was associated with an increased risk of CIPN, however other pharmacokinetic measures including maximum concentration were not associated with an increased CIPN risk ( 90 ).…”
Section: Pharmacokinetics and Cipnmentioning
confidence: 99%